Faktor-Faktor Yang Mempengaruhi Tingkat Stres Kerja Pada Karyawan Di Industri Manufaktur - Friska Dela Oktapiani; Susilawati (Gudang Jurnal Multidisiplin Ilmu, 2024)
This study analyzes the factors that affect the level of work stress in employees in the manufacturing industry sector. This study uses a quantitative approach with data collected through questionnaires distributed to employees in several manufacturing companies. Regression analysis techniques are used to evaluate the impact of various factors on work stress. In addition, demographic characteristics such as age, education, and employment status also play an important role in determining stress levels. This study recommends the need for management policies that focus on reducing workload, improving work environment conditions, and providing employee welfare programs to reduce stress and improve employee welfare. These findings provide valuable insights for manufacturing companies in their efforts to create a healthier and more productive work environment.